2-Propylamino-5-[4-(2-hydroxy-3,5-dichlorobenzylideneamino) phenyl]-1,3,4-thiadiazole: X-ray and DFT-calculated structures - KARAKUŞ, SEVGİ (SPRINGER/PLENUM PUBLISHERS, 2010)
2-Propylamino-5-[4-(2-hydroxy-3,5-dichlorobenzylideneamino) phenyl]-1,3,4-thiadiazole, formulated as C18H16Cl2N4OS (I), was synthesized. The crystal and molecular structure of (I) have been determined by H-1-NMR, IR, and X-ray single crystal diffraction. The compound (I) crystallizes in the monoclinic, space group P2(1)/c with unit cell parameters a = 9.0576(2) , b = 24.3382(8) , c = 9.0585(2) , M (r) = 407.31, V = 1851.13(9) (3), Z = 4, R (1) = 0.036, and wR (2) = 0.096. Molecular geometry from X-ray experiment of (I) in the ground state has been compared using the density functional method (B3LYP) with 6-31G(d) basis set. To determine conformational flexibility, molecular energy profile of (I) was obtained by semi-empirical (PM3) calculations with respect to selected degree of torsional freedom, which was varied from -180A degrees to +180A degrees in steps of 10A degrees. The results are indicative that the Schiff base, which contains a thiadiazole ring, prefers to be in E-configuration. In addition, molecular electrostatic potential, frontier molecular orbitals, and natural bond orbitals analysis were performed by the B3LYP/6-31G(d) method.
Keywords: 1,3,4-Thiadiazole; Schiff base; Crystal structure; Theoretical calculation; DENSITY-FUNCTIONAL THEORY; ANTITUBERCULOSIS ACTIVITY; SCHIFF-BASES; HARTREE-FOCK; EXCHANGE; APPROXIMATION; POTENTIALS; GEOMETRIES; MOLECULES; ANALOGS